2015
DOI: 10.1002/cphc.201500173
|View full text |Cite
|
Sign up to set email alerts
|

From Graphene to Carbon Nanotubes: Variation of the Electronic States and Nonlinear Optical Responses

Abstract: From the same piece of graphene sheet, (3, 3) and (6, 0) carbon nanotube clips were obtained on the basis of the different manners of rolling. The nature of the electronic state varies differently with different manners of rolling and is significantly affected by zigzag edges. The intermediate structures formed during the rolling process were functionalized with fluorine and oxygen atoms to investigate the electronic states and nonlinear optical (NLO) responses. Passivation of the intermediate structures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Actually, CNTs not only have regular structures with controllable size but also have frictionless interior surface, making themselves as fast water transporters. Although CNT lengths in some experiments were up to micrometers, a recent exciting work prepared 5–10 nm CNTs as channel models in lipid bilayer membrane, which is same to the length scale of computer simulations. Understanding the water transport properties are also related to huge applications, from molecular sieves to biosensors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, CNTs not only have regular structures with controllable size but also have frictionless interior surface, making themselves as fast water transporters. Although CNT lengths in some experiments were up to micrometers, a recent exciting work prepared 5–10 nm CNTs as channel models in lipid bilayer membrane, which is same to the length scale of computer simulations. Understanding the water transport properties are also related to huge applications, from molecular sieves to biosensors …”
Section: Introductionmentioning
confidence: 99%
“…Thus, not only our life but also life itself depends on the mass transport. During the past decade, there has been a great dedication on the transport properties of water through carbon nanotubes (CNTs) both in computer simulations and experiments . Actually, CNTs not only have regular structures with controllable size but also have frictionless interior surface, making themselves as fast water transporters.…”
Section: Introductionmentioning
confidence: 99%
“…As ideal nanochannel models, carbon nanotubes (CNTs) demonstrate extraordinary electrical, mechanical, and thermal properties. [13] In particular,p revious experiments [14,15] and simulations [16] show that CNTsa re fast water transporters, where the water flow rate exceeds the prediction of conventional nonslip hydrodynamic flow by severalo rders of magnitude.A s ar esult,i fs uch CNTsc an be utilized in the seawater desalination or polluted water filtration,t he energy required is expected to be reduced significantly,c ompared to traditional nanoporousm aterials. It has been suggested that the fast conduc-tion of water inside CNTsi sn ot only due to the regulars tructure, smooth interior surface, and hydrophobic nature of the CNTs, but also dependento nt he strong water-water and weak water-CNT interactions, as wellast he unique structures of confined water different from bulk system.…”
Section: Introductionmentioning
confidence: 99%
“…As ideal nanochannel models, carbon nanotubes (CNTs) demonstrate extraordinary electrical, mechanical, and thermal properties . In particular, previous experiments and simulations show that CNTs are fast water transporters, where the water flow rate exceeds the prediction of conventional nonslip hydrodynamic flow by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The antiferromagnetic coupling between the zigzag edges at the two ends presents. C Comparison with the rolling processes of forming (3, 3) and (6, 0) CNT clipsThe formation of (3, 3) and (6, 0) CNT clips from the same piece of F-graphene sheet (C 72 H 24 ) has been explored in our previous work 36. Different from the triplet F-graphene sheet (C 128 H 32 ) in the present work, the ground state of the F-graphene sheet (C 72 H 24 ) is open-shell singlet.…”
mentioning
confidence: 99%